MORPHOLOGICAL VARIABILITY OF INDONESIAN RICE GERMPLASM AND THE ASSOCIATED SNP MARKERS - Lestari, Puji; Utami, Dwinita Wikan; Rosdianti, Ida; Sabran, Muhamad (Emirates Journal of Food and Agriculture, 2017)
Morphological and molecular characterization of rice accessions with varied genetic background is highly considerable to be carried out to their utilization and to genetic variability incorporation into rice breeding program. In this study, the diversity within 60 rice genotypes from different cultivar groups of indica, japonica and tropical japonica cultivars was analyzed for 19 morphological traits and 384-SNPs-plex with GoldenGate assay. Principal component analysis (PCA) clustered the germplasm into two main groups (indica/japonica and indica/tropical-japonica). PCA axes 1 and 2 and morphological traits with eigen values at arbitrary above 0.2, explained 24.60% of total variation in the rice germplasm. Seven traits (leaf color, leaf sheats color, ligule color, diameter of basal internode, culm color, ligule length, and flag leaf angle) could be the potential traits as descriptors for further characterization and conservation studies in rice germplasm. Based on total morphological traits and 384 SNPs, two major clades were generated and differentiated most genotypes into cultivar group according to their individual genetic background. Of total 154 SNPs associated with 15 morphological traits, approximately 48 SNPs were highly significant associated with quantitative and quantitative traits. These alleles could provide breeders to effectively identify, track and incorporate regions of chromosomes governing the desired morphological traits to improve rice varieties in Indonesia.